The evolution of printing - Rodell, Earl Nathaniel (My University, 1903)
Introduction: In the remote antique ages man could think and his thoughts did not die with him. We have them yet, embedded in the picturesque ruins of his works of art. Yet the hieroglyphic messages were chiselled into the cold granite with much pains and labor, and it was the beholding of this infinite toil of the stone carver that caused one man to ponder. Instead of the unwieldy boulders built by nature in the ages past, he would substitute clay, moulded by the hand of man and in the moment. But the inscriptions? Here was the problem! The carver of wood came to the rescue. By means of characters first cut in the wood and then impressed into the soft, unbaked clay, the divine words of the King would remain to time immortal. Thus in the bricks of Egypt and Assyria we have the first evidences of characters reproduced by pressure, and this is the secret of printing. Also, the all-powerful Romans used stamps for producing inscriptions. The plebian marked his cattle with a punch containing his initials. The merchant put an imprint on his goods. But the time was unripe for the development of printing. The rulers imposed heavy burdens upon their subjects and the secret disclosed remained undeveloped. It was not for kings to advance the art, but rather to retard it.
Citation: Rodell, Earl Nathaniel. The evolution of printing. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Impression Printing; Block Printing; Movable Type; Coster; Gutenberg; Theses